Greater lower limb flexion in gymnastic landings is associated with reduced landing force: a repeated measures study - Slater, A.; Campbell, Amity; Smith, A.; Straker, Leon (Routledge, 2015)
High impact forces during gymnastic landings are thought to contribute to the high rate of injuries. Lower limb joint flexion is currently limited within gymnastic rules, yet might be an avenue for reduced force absorption. This study investigated whether lower limb flexion during three gymnastic landings was related to force. Differences between landings were also explored. Twenty-one elite women's artistic gymnasts performed three common gymnastic techniques: drop landing (DL), front and back somersaults. Ankle, knee, and hip angles, and vertical ground reaction force [(vGRF) magnitude and time to peak], were measured using three-dimensional motion analysis and force platform. The DL had significantly smaller peak vGRF, greater time to peak vGRF and larger lower limb flexion ranges than landing from either somersault. Peak vGRF and time to peak vGRF were inversely related. Peak vGRF was significantly reduced in gymnasts who landed with greater hip flexion, and time to peak was significantly increased with increasing ankle, knee, and hip flexion. Increased range of lower limb flexion should be encouraged during gymnastic landings to increase time to peak vGRF and reduce high impact force. For this purpose, judging criteria limitations on lower limb flexion should be reconsidered.